Recent Progresses in the Catalytic Stereoselective Dearomatization of Pyridines - Lucrezia Margherita Comparini; Mauro Pineschi (Molecules, 2023)
1,2- and 1,4-dihydropyridines and N-substituted 2-pyridones are very important structural motifs due to their synthetic versatility and vast presence in a variety of alkaloids and bioactive molecules. In this article, we gather and summarize the catalytic and stereoselective synthesis of partially hydrogenated pyridines and pyridones via the dearomative reactions of pyridine derivatives up to mid-2023. The material is fundamentally organized according to the type of reactivity (electrophilic/nucleophilic) of the pyridine nucleus. The material is further sub-divided taking into account the nucleophilic species when dealing with electrophilic pyridines and considering the reactivity manifold of pyridine derivatives behaving as nucleophiles at the nitrogen site. The latter more recent approach allows for an unconventional entry to chiral N-substituted 2- and 4-pyridones in non-racemic form.